BOOK REVIEW: DISABILITY, SOCIETY, AND THE INDIVIDUAL by JULIE SMART - BEAGAN, BRENDA; Landry, Jennifer (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
BOOK REVIEW of: DISABILITY, SOCIETY, AND THE INDIVIDUAL by JULIE SMART.